2018
DOI: 10.2967/jnumed.118.209544
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reproducibility of 18F-FDG PET/CT Uptake in Cancer Patients Within a Qualified and Calibrated Local Network

Abstract: Calibration and reproducibility of quantitative 18 F-FDG PET measures are essential for adopting integral 18 F-FDG PET/CT biomarkers and response measures in multicenter clinical trials. We implemented a multicenter qualification process using National Institute of Standards and Technology-traceable reference sources for scanners and dose calibrators, and similar patient and imaging protocols. We then assessed SUV in patient test-retest studies. Methods: Five 18 F-FDG PET/CT scanners from 4 institutions (2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…2 ), which we previously defined as the acceptable margin of error. Of note, a recent study by Kurland et al [ 17 ] demonstrated that lesion uptake (SUVmax) showed an average difference of 8% for the same scanner model within the same institution and 18% for different scanners from different institutions. No notable differences were observed between SUVmax and SUVpeak measurements and between low, moderate and high tracer uptake.…”
Section: Discussionmentioning
confidence: 99%
“…2 ), which we previously defined as the acceptable margin of error. Of note, a recent study by Kurland et al [ 17 ] demonstrated that lesion uptake (SUVmax) showed an average difference of 8% for the same scanner model within the same institution and 18% for different scanners from different institutions. No notable differences were observed between SUVmax and SUVpeak measurements and between low, moderate and high tracer uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed imaging signature should be further tested in independent, prospective studies. Issues such as repeatability and reproducibility should be addressed for multicenter validation as proposed in previous studies (41)(42)(43). Another limitation is that the cohort includes both HPV-positive and HPV-negative tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A high test-retest interclass correlation coefficient (ICC) of 0.90 and 0.91 was found for SUV max and SUV mean , respectively. Reproducibility across different scanners was assessed in 23 patients, 17 with BC [13]. Patients underwent two [ 18 F]-FDG-PET/CT scans within 15 days on the same scanner or on different scanners at different sites.…”
Section: Development Stages Of [ 18 F]-fdg-pet/ctmentioning
confidence: 99%